New Trends In Arabic Novels In The Current Era/ الاتجاهات الجديدة في الروايات العربية في العصر الحالي - Farah, Lubna; Shahzad, Muhammad Khurram (Jurnal Bahasa Arab, 2024)
This study explores the new trends in contemporary Arabic novels, analyzing the thematic and stylistic shifts that characterize modern Arabic literature. The research highlights several emerging trends, including the diversification of themes, stylistic innovation, cultural hybridity, and the integration of technology into narrative forms. The study discusses how modern Arabic novels have expanded beyond traditional topics like love and politics to include more complex issues such as identity, migration, gender, and the impact of globalization. The research method used is a literature study by analyzing contemporary Arabic novels. The results show that stylistically, there has been a move towards more experimental approaches, with authors adopting fragmented structures, multi-layered narratives, and blending of genres. The incorporation of cultural influences from the West and the East has also enriched the content of Arabic novels, reflecting the multicultural experiences of modern Arab writers. Additionally, the use of digital platforms and technologies in storytelling is reshaping the narrative landscape, offering new methods for engaging readers. Through an analytical lens, this study offers a comprehensive look at how Arabic novels are evolving to reflect contemporary societal changes and global cultural interactions.